Media Hegemony and Political Scandal: The Narrative of Ridwan Kamil Alleged Affair in the Vortex of Power - Aminudin, Amin (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
In the realm of politics, scandals involving public figures often attract significant attention, especially when reported by the media. One major scandal that once stirred public discourse was the alleged affair involving Ridwan Kamil. The media plays a crucial role in shaping public perception of political figures, often through news reporting constructed with specific narratives. This study aims to explore how the media constructs narratives surrounding the alleged affair of Ridwan Kamil, and how it utilises its influence to shape public opinion and reinforce power structures through such reporting. Using Antonio Gramsci’s theory of hegemony, this research analyses how major Indonesian media outlets, such as Kompas.com, Detik.com, and CNN Indonesia, presented news coverage of this scandal. It also examines how the media frames the news in ways that influence the public’s perception of Ridwan Kamil and his political standing. The method employed is discourse analysis, focusing on the texts and narratives built by the media. This research not only investigates what is reported but also how the reporting itself constructs public perception and discourse. The findings reveal that scandals related to personal morality have significant destructive potential, as Indonesian society still views political leaders as moral figures. The clear polarisation of public opinion in Ridwan Kamil’s case is not solely caused by the content of the news but also by the selective consumption of information facilitated by social media algorithms. This study also identifies character assassination as a political communication strategy used to damage reputations by attacking personal aspects. Ideological bias in media coverage aligns with Herman and Chomsky’s propaganda model, where the media serves the interests of capital owners and those in power.